Pengaruh Halal Awareness, Brand Image, dan Religiusitas terhadap Keputusan Pembelian Konsumen Mie Gacoan Yogyakarta - Puspitasari, Arnetta Aulia; Rokhman, Nur (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2024)
This research aims to analyze the influence of halal awareness, brand image, and religiosity on consumer purchasing decisions of Mie Gacoan Yogyakarta. This research was conducted in January 2023 on consumers Mie Gacoan Yogyakarta. The data collection is by using Google Forms. The population in this research were.all customers who had visited and purchased Mie Gacoan Yogyakarta products. The sampling technique uses the Non-Probability Sampling model with a purposive sampling method, that is determining the sample with the consideration that consumers has made at least 1 (one) purchase of Mie Gacoan Yogyakarta products. The results of this research indicate that halal awareness have a positive. and not significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, and religiosity has a positive and significant effect on purchasing decisions